Detection radius of EMG for fasciculations: Empiric study combining ultrasonography and electromyography. Issue 2 (February 2018) - Regensburger, Martin; Tenner, Felix; Möbius, Cornelia; Schramm, Axel
Highlights: Simultaneous EMG and muscle ultrasonography improves characterization of fasciculations. All fasciculations detected by EMG were also observed on ultrasonography. Mean detection radius of EMG for fasciculations was 7.75 mm. Abstract: Objective: The aims of this study were to investigate the detection radius and sensitivity of EMG for fasciculations. Methods: Muscle ultrasonography was performed simultaneously to EMG recordings in patients with fasciculations in the context of amyotrophic lateral sclerosis. Ultrasonography and EMG parameters were analyzed for selected fasciculations. Results: A total of 381 fasciculations were detected by ultrasonography in 18 muscles of 10 patients. Out of these, 125 (33%) were EMG-negative. In contrast, none of the fasciculations detected by EMG were ultrasonography-negative. EMG detection probability decreased significantly with increasing distance from the center of the fasciculation. EMG detection rate was 98% when the EMG needle was located within the fasciculation and 50% at 7.75 mm distance from the fasciculation center. In addition, EMG detection depended significantly on cross-sectional area of the fasciculation and presence of neurogenic changes. Conclusions: For detecting the same fasciculations, EMG is less sensitive than ultrasonography. EMG detection probability decreases sharply at a distance comparable to motor unit size. Significance: These results extend previous knowledge about superior sensitivity of ultrasonography for fasciculations. Moreover, our novel bimodal detection method provides first in vivo data about the EMG detection radius for fasciculations in a clinical setting.